Tantangan Dakwah di Era Disrupsi Perspektif Psikologi Sosial - Tanuri (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2024)
In the era of technological and informational disruption, the practice of dakwah as a form of religious communication faces various complex challenges. This research explores the challenges of dakwah in the era of technological and informational disruption, with a focus on the perspective of social psychology. Qualitative methods are employed to comprehend the impact of technology on dakwah and the psychological dynamics involved in the process. The study examines changes in behavior and societal perceptions towards dakwah, as well as the role of social media and technology in shaping attitudes towards dakwah messages. Through the identification of effective psychological strategies, this research demonstrates that the social psychological aspect plays a crucial role in addressing the challenges of dakwah arising from technological disruption. The implications of these findings support the development of adaptive and responsive dakwah strategies to the evolving social changes in modern society. Additionally, this research provides insights into the role of social psychology in religious communication in the continually evolving technological era.